Production of 26-deoxymonensins A and B by Streptomyces cinnamonensis in the presence of Metyrapone - Pospísil, S; Sedmera, P; Havlícek, V; Tax, J (Applied and environmental microbiology, 1994)
Metyrapone, a potent cytochrome P-450 inhibitor, added at 9 mM to a submerged culture of Streptomyces cinnamonensis caused partial inhibition of total monensin biosynthesis and coproduction of new metabolites, 26-deoxymonensins A and B. The latter was isolated as its 25-O-methyl derivative. Metyrapone was simultaneously reduced to metyrapol. All of these compounds were identified by nuclear magnetic resonance spectroscopy and mass spectrometry.
Keywords: pyridiny; metyrapon; Monensin; monensin; antibakteriální látky; Pyridines; hmotnostní spektrometrie; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Metyrapone; Anti-Bacterial Agents; Mass Spectrometry; Streptomyces